Actinomyces meyeri pleural infection that was difficult to treat due to delayed culture: A case report and literature review of 28 cases. (2021) - Shimoda, Masafumi; Tanaka, Yoshiaki; Kokutou, Hiroyuki; Furuuchi, Koji; Osawa, Takeshi; Morimoto, Kozo; Yano, Ryozo; Yoshimori, Kozo; Ohta, Ken
Abstract: An eighty-three-year-old man suffered from cough, right chest pain, and progressive dyspnea for sixteen days. He had hypoxemia, high white blood cells and C-reactive protein, and moderate right-sided pleural effusion on radiographic imaging. A pleural fluid examination revealed exudate. He was diagnosed with pleural infection and treated with intravenous ampicillin/sulbactam. On the second day of hospitalization, the treatment was changed to levofloxacin and clindamycin due to drug eruption. He improved gradually and was prescribed only oral levofloxacin on the eighteenth day of hospitalization. However, improvements in inflammation and imaging findings were poor. Actinomyces meyeri resistant to fluoroquinolones was cultured from a pleural effusion sample on the twenty-sixth day of hospitalization. The treatment was changed to oral clindamycin, and his medical condition subsequently improved. We reviewed twenty-eight patients with Actinomyces pleural infection and thirty-eight patients with other pleural infection phenotypes from our hospital and published case reports. Actinomyces pleural infection is a long-term process and results in a large amount of pleural effusion compared to other pleural infection phenotypes. These results might be related to the fact that Actinomyces is a slow-growing organism.